Evaluation of a Beta-Blocker–Edema–Loop Diuretic Prescribing Cascade: A Prescription Sequence Symmetry Analysis. (1st February 2022) - Vouri, Scott Martin; Morris, Earl J; Jiang, Xinyi; Hofer, Ann-Kathrin; Schmidt, Stephan; Pepine, Carl; Winterstein, Almut G; Smith, Steven M
Abstract: BACKGROUND: Drug-related adverse events associated with antihypertensive therapy may result in subsequent prescribing of other potentially harmful medications, known as prescribing cascades. The aim of this study was to assess the magnitude and characteristics of a beta-blocker–edema–loop diuretic prescribing cascade. METHODS: A prescription sequence symmetry analysis was used to assess loop diuretic initiation before and after initiation of beta-blockers among patients 20 years or older without heart failure, atrial fibrillation, other arrythmias, or use of calcium channel blocker within a U.S. private insurance claims database (2005–2018). The temporality of loop diuretic initiation relative to a beta-blocker or negative control (renin-angiotensin system blocker) initiation was tabulated. Secular trend-adjusted sequence ratios (aSRs) with 95% confidence intervals (CIs) compared the initiation of loop diuretic 90 days before and after initiation of beta-blockers. RESULTS: Among 988, 675 beta-blocker initiators, 9, 489 patients initiated a new loop diuretic prescription 90 days after and 5, 245 patients before beta-blocker initiation, resulting in an aSR of 1.78 (95% CI, 1.72–1.84). An estimated 1.72 beta-blocker initiators per 100 patient-years experienced the prescribing cascade in the first 90 days. The aSR was disproportionately higher among older adults (aSR 1.97), men (aSR 2.25), and patients who initiated metoprolol tartrate (aSR 2.48), labetalol (aSR 2.18), or metoprolol succinate (aSR 2.11). Negative control results (aSR 1.09, 95% CI, 1.05–1.13) generally corroborated our findings, but suggested modest within-person time-varying confounding. CONCLUSIONS: We observed excess use of loop diuretics following beta-blocker initiation that was only partially explained by secular trends or hypertension progression. Graphical Abstract: